Conservation issues in modern and contemporary murals - Sánchez Pons, Mercedes; Shank, Will; Fuster López, Laura (Cambridge Scholars Publishing, 2015)
This volume represents a forum for conservators, conservation scientists, artists and heritage managers. It includes the voices of many of the different partners involved in the complex task of preserving artworks:The vital experience of artists who create murals and are sometimes asked to treat their creations;Theoretical reflections on how to deal methodologically with conservation;Scientific studies on the identification of constituent materials and/or on the development of procedures for their preservation;The opinion of cultural managers;The specific experiences of conservators.All of the.